Peranan dan tanggungjawab wakil rakyat dalam sistem politik Malaysia - Malike, Brahim (2014)
The aim of this research is to study the roles and responsibilities of elected representative in Malaysia. In reality, the people were confused to understand the formal or informal roles of elected representative, as their roles are too complex and challenging. Therefore, this research was conducted to: (i) evaluate the evolution of elected representative’s institution from pre-independence era to the 12th term; (ii) classify their roles by the primary and secondary category of responsibilities; (iii) evaluate their roles in the socio-economic and political; (iv) and analyse the issues and challenges faced by them in Malaysia. In answering the research objectives, this research used primary and secondary data. The primary data were obtained through questionnaires, while the secondary data were obtained from books, journals, newspapers, and also from past studies. Respondents were chosen through purposive sampling, which involved members of Parliament and State Legislative Assembly. To guide the analysis, the political leadership and parliamentary democracy conceptual framework were used. From the analysis, there were three categories of primary roles of elected representative identified. First, parliamentary responsibilities were formal and substantial roles as representatives, legislators, backbenchers, caucus members, and whips in the legislative. Second, constituency responsibilities were informal roles to provide social services to the people. Third, they also have responsibilities to the political party, with the aims to win the election and form the government. Meanwhile, the secondary roles were complementing the primary roles. It is related to the constituency responsibilities and they could communicate and knew directly the socioeconomy and development issues faced by the people. It could be evaluated through their participations and involvements in statutory body, government-linked company, non-governmental organisation and voluntary association. Analysis also found they faced various issues and challenges when implementing primer and secondary roles such as crime, unemployment, leadership conflicts, economic depression, and so forth. As a leader, elected representatives should improve their leadership quality to deliver the best services to the people. Thus, the research findings show the elected representatives have capabilities to implement primary and secondary roles effectively as a politician, leader, administrator and manager in the Malaysian political context.